Making the case for investment in public health: experiences of Directors of Public Health in English local government - Willmott, M. (J Public Health (Oxf), 2016)
BACKGROUND: Amid local government budget cuts, there is concern that the ring-fenced public health grant is being appropriated, and Directors of Public Health (DsPH) find it difficult to make the case for investment in public health activity. This paper describes what DsPH are making the case for, the components of their case and how they present the case for public health. METHODS: Thirteen semi-structured telephone interviews and a group discussion were carried out with DsPH (November 2013 to May 2014) in the Southern region of England. RESULTS: DsPH make the case for control of the public health grant and investing in action on wider determinants of health. The cases they present incorporate arguments about need, solutions and their effectiveness, health outcomes, cost and economic impact but also normative, political arguments. Many types of evidence were used to substantiate the cases; evidence was carefully framed to be accessible and persuasive. CONCLUSIONS: DsPH are responding to a new environment; economic arguments and evidence of impact are key components of the case for public health, although multiple factors influence local government (LG) decisions around health improvement. Further evidence of economic impact would be helpful in making the case for public health in LG.